2019
DOI: 10.1530/eje-18-0601
|View full text |Cite
|
Sign up to set email alerts
|

A new p.(Ile66Serfs*93) IGF2 variant is associated with pre- and postnatal growth retardation

Abstract: Objective: The IGF/IGF1R axis is involved in the regulation of human growth. Both IGF1 and IGF2 can bind to the IGF1R in order to promote growth via the downstream PI3K/AKT pathway. Pathogenic mutations in IGF1 and IGF1R determine intrauterine growth restriction and affect postnatal body growth. However, to date, there are only few reports of pathogenic IGF2 mutations causing severe prenatal, as well as postnatal growth retardation. Results: Here we describe a de novo c.195delC IGF2 variant (NM_000612, p.(Ile6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Body asymmetry, a frequent characteristic in SRS caused by mosaic IC1 hypomethylation, was absent in the index patient and his affected mother. This is in agreement with the previous clinical findings in patients with the p.Arg279Leu variant [4,5], the sporadic case from Japan [6] and other patients with SRS and genomic mutations of IGF2 which were not mosaic [20][21][22][23][24]. In agreement with a previous report [5], IGF-1 serum levels were normal in the index patient and his mother.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Body asymmetry, a frequent characteristic in SRS caused by mosaic IC1 hypomethylation, was absent in the index patient and his affected mother. This is in agreement with the previous clinical findings in patients with the p.Arg279Leu variant [4,5], the sporadic case from Japan [6] and other patients with SRS and genomic mutations of IGF2 which were not mosaic [20][21][22][23][24]. In agreement with a previous report [5], IGF-1 serum levels were normal in the index patient and his mother.…”
Section: Discussionsupporting
confidence: 93%
“…Since the first report of a genomic IGF2 mutation in familial SRS by Begemann et al [ 12 ], eleven additional IGF2 mutations in only sporadic cases were reported [ 13 , 20 24 ]. This number is not high, but higher than the three families and one sporadic case reported with genomic CDKN1C mutations and SRS ([ 4 6 ], this study).…”
Section: Discussionmentioning
confidence: 99%
“…Correct dosage of placental imprinted genes is critical to both functions [4,10,15,17]. However, while placental misexpression of individual imprinted genes affects conceptus growth in predictable and repeatable directions [60,61], effects on maternal behaviour and physiology are considerably less studied and can differ across studies [25,27]. To our knowledge, the effects of altered placental expression on wild-type female mice have been tested for only three imprinted genes: Peg3 , Grb10 and Phlda2 [25,26,28,30].…”
Section: Discussionmentioning
confidence: 99%
“…Through exome analysis, the authors identified an IGF2 nonsense mutation in all patients, inherited from their healthy fathers (OMIM 616489) (51). After this first report, other five studies identified variants in IGF2 gene on the paternal allele causing SRS-like (52)(53)(54)(55)(56). Up to now, one missense and six loss-of-function variants (3 frameshift, 2 nonsense and 1 splice-site) in the IGF2 gene were reported.…”
Section: Igf2 Defectsmentioning
confidence: 98%
“…Five probands presented cardiac abnormalities, including patent ductus arteriosus and atrial or ventricular septal defects. Male genital abnormalities, as hypospadia, penoscrotal transposition, cryptorchidism and ambiguous genitalia were also reported (51)(52)(53)56).…”
Section: Igf2 Defectsmentioning
confidence: 99%